From Dependence to Autonomy: The Rise of the Independent Station Model in Cross-Border E-Commerce, Its Theoretical Challenges and the Restructuring of Trade Intermediary Functions - Chen, Yanlin (Transactions on Social Science, Education and Humanities Research, 2026)
This paper systematically reviews the core issues, theoretical progress and cutting-edge trends in the research on the independent station model of cross-border e-commerce. The model is breaking the monopoly of traditional third-party platforms, allowing companies to construct global brands, and addressing fundamental issues in international trade theory, including platform dependency and trade intermediation. It consolidates studies from the past five years along three strands - driving forces, theoretical challenges, and intermediary restructuring. Findings reveal that the independent site model emerges from the low technical barrier, high cost of platforms, and the high demand for brand autonomy. Game theory indicates that adopting independent stations is a dominant strategy for enterprises. Economic sociology reveals sellers’ shift from platform dependence to operational autonomy, while intermediary functions transform from platform-integrated “black boxes” to unbundled service ecosystems. The research to date is limited due to underdeveloped theory, scant empirical analysis, insufficient dynamic considerations, and little policy analysis. From a theoretical perspective, future research should focus on digital trade intermediary theory, use micro-data, follow firm transitions, and provide policy support. This will establish a theoretical and empirical basis for the restructuring of intermediaries and the internationalization of firms in the digital trade.
Keywords: Cross-border E-Commerce; Independent Station; Platform Dependence; Trade Intermediary; Digital Trade.